A phase 2, multicentre, single-arm, open-label study to evaluate the safety and efficacy of single-agent lenalidomide (Revlimid®) in subjects with relapsed or refractory peripheral T-cell non-Hodgkin lymphoma: The EXPECT trial - Morschhauser, Franck; Fitoussi, Olivier; Haioun, Corinne; Thieblemont, Catherine; Quach, Hang; Delarue, Richard; Glaisner, Sylvie; Gabarre, Jean; Bosly, André; Lister, John; Li, Ju; Coiffier, Bertrand (European journal of cancer (1990), 2013)
This multicentre, single-arm, open-label phase 2 trial investigated the efficacy and safety of lenalidomide monotherapy in patients with relapsed/refractory peripheral T-cell lymphoma (PTCL). Patients received oral lenalidomide 25mg once daily on days 1–21 of each 28-day cycle for a maximum of 24months, until disease progression or development of unacceptable adverse events (AEs). The primary end-point was efficacy; safety was evaluated as a secondary end-point. This study was registered with ClinicalTrials.gov, number NCT00655668. A total of 54 patients with PTCL were treated. The overall response rate was 22% (12 of 54), including complete response (CR) or unconfirmed CR (CRu) in 11% of patients; 31% of patients with angioimmunoblastic T-cell lymphoma (AITL) responded (CR/CRu in 15% of patients). The median progression-free survival and median response duration were 2.5 and 3.6months, respectively, in the intent-to-treat population, and 4.6 and 3.5months, respectively, in patients with AITL. Thrombocytopenia and neutropenia were the most common grade 3 or 4 haematological AEs, in 11 (20%) and 8 (15%) patients, respectively. Overall, 19 patients (35%) experienced at least 1AE leading to study dose interruption or reduction (commonly neutropenia or thrombocytopenia). Serious AEs were observed in 54% of patients and 12 patients died during the study; lymphoma progression (n=6); and acute respiratory distress syndrome, dyspnea, lung infiltration, neutropenic sepsis, pneumonia and cerebral ischaemia (n=1 each). Lenalidomide exhibited single-agent activity in heavily pretreated patients with PTCL, particularly in patients with AITL. Future development is warranted in specific histologies, such as AITL, and in combination with chemotherapy or other agents considered active in PTCL. Celgene Corporation.